Quality of life in patients with adhesive capsulitis and diabetes mellitus (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Adhesive capsulitis is a common and disabling musculoskeletal complication in diabetes mellitus, often affecting the dominant shoulder. This results in significant pain, limited movement, and decreased quality of life (QoL). This study aimed to evaluate the stage-specific effects on QoL in diabetic patients with adhesive capsulitis of the dominant shoulder.Methods: This cross-sectional study was carried out over six months at a tertiary care hospital in Bangladesh. Diabetic patients with adhesive capsulitis of the right shoulder were included. Pain, disability, and quality of life were assessed using the Visual Analogue Scale, shoulder pain and disability index, disabilities of the arm, shoulder and hand score, and the Short-Form Health Survey (SF-36). Data were analysed using nonparametric tests, correlation analysis, and multiple linear regression.Results: Among 80 participants, most were in the freezing stage (77.5%). This stage was marked by the most severe pain [mean (standard deviation) Visual Analogue Scale: 7.5 (0.9)] and the highest overall upper-limb disability [mean (standard deviation ) disabilities of the arm, shoulder and hand: 80.3 (6.3)]. The frozen stage also showed the most significant shoulder-specific disability [mean (standard deviation ) shoulder pain and disability index-Disability: 76.0 (4.3)] and the lowest scores on the SF-36 physical 30.9 (3.7) and mental 28.1 (0.5) components. Regression analysis identified the SF-36 physical component summary as the strongest predictor of mental health-related QoL (β=0.900, P